1986
DOI: 10.1524/ract.1986.39.3.139
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Pu(IV)-Colloid by the Alpha-reduction of Pu(V) or Pu(VI) in Aqueous Solutions

Abstract: The effects of alpha-particle self-irradiation have been investigated in solutions of "'Pu in the pH range from 1.3 to > 2.2. The ionic strengths of the solutions ranged from 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 9 publications
3
37
1
Order By: Relevance
“…Pu 4f binding energies for the colloidal material are very similar to those observed for the hydroxide compound. This is not surprising, since colloidal Pu(IV) is thought to be composed of extended polymer-like hydroxylated Pu oxides, in which different O ligands will form different types of bonds with Pu [18][19][20]. Water may also be a component of this material and is consistent with the greater intensity observed at higher binding energies in the O 1s region.…”
Section: Various Pu(iv) Oxidesmentioning
confidence: 63%
“…Pu 4f binding energies for the colloidal material are very similar to those observed for the hydroxide compound. This is not surprising, since colloidal Pu(IV) is thought to be composed of extended polymer-like hydroxylated Pu oxides, in which different O ligands will form different types of bonds with Pu [18][19][20]. Water may also be a component of this material and is consistent with the greater intensity observed at higher binding energies in the O 1s region.…”
Section: Various Pu(iv) Oxidesmentioning
confidence: 63%
“…In supersaturated J-13 well water (or other solutions) with plutonium (or americium), radionuclides, themselves, form radiocolloids (Nitsche, 1991a;Ramsay, 1988;Newton et al, 1986;Kim, 1986;Buckau et al, 1986;Olofsson et al, 1983;Benes et al, 1979;Cleveland, 1979). They are of polymeric hydroxide phases and can be very small (< 1 nm) and may not grow.…”
Section: Immersion Test Resultsmentioning
confidence: 99%
“…For instance, in HLW glass leaching, Transmission Electron Microscopy studies showed that condensation takes place in static immersion tests for the formation of radioactive clay colloids . Also, actinide condensation for true radiocolloids is well recognized in solubility tests or related work in supersaturated leachates (Nitsche, 1991a;Ramsey, 1988;Kim, 1986;Newton et al, 1986;Olofsson et al, 1983;Rai and Ryan, 1982;Benes et al, 1979;Cleveland, 1979).…”
Section: Condensation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidizing chlorine species are presumably responsible for the reported oxidation of Pu(IV) to Pu(VI) in chlorinated drinking water (Larsen and Oldham, 1978). Conversely, in other aqueous media, radiolytically produced peroxide and other radicals promote Pu(VI) reduction over time (Newton et al, 1986). Pu(V) in turn disproportionates to form Pu(IV) and Pu(VI) at a variable rate dependent upon factors including Pu concentration, solution pH, and other impurities present in solution (Rabideau, 1957).…”
Section: Introductionmentioning
confidence: 99%